When the smoke cleared: Tobacco supply and consumption by the British Expeditionary Force, 1914-1918 - Henry Daniels (Revue Française de Civilisation Britannique)
The changing image and eventual triumph of the cigarette over other forms of tobacco consumption during the fifty years prior to the Great War and its supply to British troops on the Western Front 1914-18 are examined here, along with with abundant examples of branding and packaging materials illustrative of the different types of appeal manufacturers sought to associate with cigarette smoking.